COMPARATIVE EVALUATION OF EFFECT OF INCISAL PREPARATION DESIGN ON FRACTURE RESISTANCE OF TWO DIFFERENT COMPOSITE VENEERS: AN IN-VITRO STUDY - Dr. Sai Krishna Manchala; Dr. M. Pratap kumar; Dr. P. Samba Shiva Rao; Dr. R. Janavathi; Dr. J. Deepa; Dr. K. Sowmya (The Bioscan, 2024)
Background: To evaluate the fracture resistance of two different composite veneers with two different preparation designs. Materials and Methods: A total of 60 extracted human maxillary central incisors were prepared and divided into two groups based on the type of composite veneer material: Group I: Filtek Z250 XT (n = 30), Group II: CHARISMA R Smart (n = 30). They were further divided into two subgroups based on the incisal preparation design: Subgroup A: Butt joint (n = 15), and Subgroup B: Incisal overlap-palatal chamfer (n = 15). Standard veneer preparations were done and composite veneers were fabricated with the respective composites. All the specimens were mounted on acrylic blocks and loaded to failure using a Universal testing machine (UTM). Statistical analysis: The obtained data were statistically analysed using the Mann-Whitney U test. Results: Filtek Z250 XT with incisal overlap (Group I subgroup B) showed higher fracture resistance followed by Filtek Z250 XT with butt joint. Conclusion: It was concluded that Filtek Z250 XT has a higher fracture resistance than CHARISMA R Smart and incisal overlap preparation has a higher fracture resistance than butt joint preparation.